Purification and characterization of a novel and conserved TPR-domain protein that binds both Hsp90 and Hsp70 and is expressed in all developmental stages of Leishmania major - Araujo, Sara A.; Martins, Gustavo H.; Quel, Natalia G.; Aragao, Annelize Z. B.; Morea, Edna G. O. [UNESP]; Borges, Julio C.; Houry, Walid A.; Cano, Maria I. N. [UNESP]; Ramos, Carlos H. (Elsevier B.V., 2021)
Heat shock proteins (Hsps) are involved in several important aspects of the cell proteostasis. Hsp90 interacts with at least a tenth of the cell proteome helping a large number of proteins to fold correctly. Hsp90 function is modulated by several co-chaperones having TPR (tetratricopeptide repeat) domains that allow for interaction with the C-terminal MEEVD motif of the chaperone. Another important chaperone, Hsp70, has a C-terminal EEVD motif that binds to TPR. Leishmania is a protozoan that causes leishmaniasis, a neglected disease in humans and other animals. There is still no effective treatment for leishmaniasis, however the study of structure and function of the proteins of the parasite may generate potential targets for future therapeutic intervention studies. In this work, the genome of Leishmania major was searched for a novel TPR-domain gene, which is conserved in Leishmania. The recombinant protein, LmTPR, was produced in pure and folded state and was characterized by biophysical tools as a monomer with an elongated conformation. Studies in Leishmania major were also preformed to complement these in vitro experiments. Splice Leader RNA-seq analysis and Western blot indicated that the protein was expressed in all developmental stages of the parasite. Binding assays confirmed that both Hsp90 and Hsp70 bind specifically to LmTPR. Finally, sequence and structural predictions indicated a C terminal region as a RPAP3 domain. Altogether, this study identified a novel TPR-domain co-chaperone of Hsp90 that is conserved and expressed in all developmental stages of Leishmania major. (C) 2021 Elsevier B.V. and Societe Francaise de Biochimie et Biologie Moleculaire (SFBBM). All rights reserved.
Keywords: TPR-Domain protein; Leishmania major; Hsp90 co-chaperones; Protein folding; Protein structure and function